Factors Associated with the Utilization of Institutional Delivery Service among Mothers - Pathak, Pratima; Shrestha, Shovana; Devkota, Rashmi; Thapa, Basanta (Journal of Nepal Health Research Council, 2018)
Background: Assessment of utilization of institutional delivery services is crucial to reduce risk of maternal mortality and morbidity in countries like Nepal. This study was conducted to find out the proportion of utilization of institutional delivery service and associated factors among mothers.Methods: Data was collected from the total of 129 mothers of Kathar VDC, Chitwan district who delivered baby within last one year proceeding the period of data collection using census method. Descriptive statistics and binary logistic regression analysis were applied.Results: Out of 129 mothers, 78.3% had their delivery in the health facilities. Binary logistic analysis showed number of factors associated with utilization of institutional delivery service such as ethnicity, respondents educational level, number of pregnancy, number of ANC visit and birth preparedness status. But in the multivariable logistic regression analysis, no. of ANC visit (AOR = 10.03, 95 % CI = 1.02-98.29) was only independent factors affecting institutional delivery service utilization.Conclusions: A number of factors have been shown to affect the utilization of institutional delivery. Therefore, concerned authority should plan and implement awareness programme aiming at increasing antenatal clinic visits and utilization of institutional delivery service.